2022
DOI: 10.1002/gcc.23038
|View full text |Cite
|
Sign up to set email alerts
|

Molecular investigation of ALK‐rearranged epithelioid fibrous histiocytomas identifies CLTC as a novel fusion partner and evidence of fusion‐independent transcription activation

Abstract: Epithelioid fibrous histiocytoma (EFH) is a rare cutaneous neoplasm, which is characterized by the presence of rearrangements involving the ALK gene. Although EFH was long considered a variant of fibrous histiocytoma, the identification of its unique genetic signature confirmed that it represents a distinct entity. The aim of the present study was to examine a cohort of ALK‐immunoreactive EFH cases to further characterize gene fusion partners. Next generation sequencing detected ALK fusions in 11 EFH cases ide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…By analogy, a similar mechanism might play a role in EFH. The morphological findings in our case closely resemble those of both cases with CLTC - ALK fusions described by Georgantzoglou et al, who have identified the CLTC gene as a novel fusion partner of the ALK gene in two cases of EFH [ 6 ]. Indeed, both types of EFH were associated with predominantly fusiform to dendritic cells, instead of epithelioid cells, arranged in a whorled fashion, showing no exophytic growth or epidermal collarette and lacking a prominent capillary component.…”
Section: Discussionsupporting
confidence: 88%
“…By analogy, a similar mechanism might play a role in EFH. The morphological findings in our case closely resemble those of both cases with CLTC - ALK fusions described by Georgantzoglou et al, who have identified the CLTC gene as a novel fusion partner of the ALK gene in two cases of EFH [ 6 ]. Indeed, both types of EFH were associated with predominantly fusiform to dendritic cells, instead of epithelioid cells, arranged in a whorled fashion, showing no exophytic growth or epidermal collarette and lacking a prominent capillary component.…”
Section: Discussionsupporting
confidence: 88%
“…Certain fusion partners such as TPR and KANK1 , however, are associated with high‐grade spindled and pleomorphic morphology and aggressive behavior 1 . VCL::ALK fusion in the central nervous system has been reported as “epithelioid inflammatory myofibroblastic sarcoma,” 3 and is also found in variants of renal cell carcinoma (especially with sickle cell trait) 4–6 and epithelioid fibrous histiocytoma (EFH) 4–6 . It is true that superficial dermal tumors may exhibit better behavior than deep counterparts, as these may be detected earlier at a smaller size with complete excision, yet these are classified by the repertoire of reproducible features.…”
Section: Discussionmentioning
confidence: 99%
“…ALK‐immunoreactivity is detected in 88% of EFH, but is not present in benign fibrous histiocytoma or its variants. The most prevalent ALK fusions detected in EFH are SQSTM1‐ALK and VCL‐ALK , 4,7,9,13 although EML4 and TMP3 fusion partners may be observed. This tumor is confined to the upper dermis in older adults and does not have myoid stroma, deep dermal involvement, moderate cellularity, or focal S100 protein staining of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations